2022
DOI: 10.1186/s12876-022-02346-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of esophageal perforations in infants by endoscopic vacuum therapy: a single center case series

Abstract: Background Endoscopic vacuum therapy (EVT) has become a standard treatment method for esophageal perforations in adults. However, experience with EVT in infants is scarce. In this retrospective case series, we report on four very young infants who were successfully treated with EVT for esophageal perforations of different etiology. Methods Four infants were diagnosed with esophageal perforations on day 7, 32, 35 and 159 of life, respectively. The y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A preexisting gastrostomy site was re‐accessed to allow for a novel approach for endoluminal sponge placement in E‐VAC therapy by gastrostomy‐assisted pull technique. Although primary closure remains standard of care for esophageal perforation, others include medical management, drainage, and many cases can be successfully treated with endoscopic intervention with stent placement 5–7 . EVAC demonstrated greater success in healing surgical anastomotic perforations over stenting and has been used for gastrointestinal leaks, fistulas, and perforations within pediatric patients 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preexisting gastrostomy site was re‐accessed to allow for a novel approach for endoluminal sponge placement in E‐VAC therapy by gastrostomy‐assisted pull technique. Although primary closure remains standard of care for esophageal perforation, others include medical management, drainage, and many cases can be successfully treated with endoscopic intervention with stent placement 5–7 . EVAC demonstrated greater success in healing surgical anastomotic perforations over stenting and has been used for gastrointestinal leaks, fistulas, and perforations within pediatric patients 5 .…”
Section: Discussionmentioning
confidence: 99%
“…EVAC demonstrated greater success in healing surgical anastomotic perforations over stenting and has been used for gastrointestinal leaks, fistulas, and perforations within pediatric patients 5 . EVT functions by connecting a polyurethane sponge or porous film to a suction catheter that is either intraluminally placed via endoscopy, or via intracavitary placement by insertion into the perforation site to cover the region of perforation 7 . This creates negative pressure therapy at the perforation site, causing a collapse of surrounding tissue forming the seal, which stimulates granulation of the wound to promote closure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…During EVT, the patients remained NPO, and parenteral nutrition was provided until the absence of leaks is verified. Fasting is considered in these patients because oral nutrition would contaminate both the perforation site and the sponge, rendering EVT ineffective [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The pressure ranges between 75 and 150 mmHg. A pressure of 75 mmHg is considered low intensity, 125 mmHg of medium intensity, and 150 mmHg as high intensity in pediatric patients [7]; in neonates, we apply 75-100 mmHg, and chest drainage is maintained (Fig. 1).…”
Section: Techniquementioning
confidence: 99%
“…Kaczmarek et al [ 10 ] specifically looked at infants at 7-159 days of life and found that in all four of their cases, EVAC led to complete EP closure after 22 days and an average of 4.5 EVAC exchanges. Fraga et al looked at an eight-month-old male with esophageal perforation after a video-assisted thoracoscopic lobectomy for a right lower lobe congenital malformation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%